Peran Mahasiswa Dalam Pendidikan Lingkungan: Pembuatan Sabun Cair Eco Enzyme dalam Meningkatkan Kesadaran Ekologis bagi Siswa SMA - Bima Setya; M. Fynzer Verollino; Nauf Hanifah; Erlisa Dwiyanti; Nadia Meisya Putri (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
Waste management, particularly organic waste, remains a significant environmental challenge in Indonesia, with household and school waste being major contributors. This community service initiative, conducted by the Dharma Sevavigyana Community of Universitas 17 Agustus 1945 Semarang, aimed to enhance ecological awareness among high school students through the production of eco-enzyme liquid soap. The program, held at SMA Negeri 16 Semarang, combined conceptual education with practical training to teach students how to transform organic waste into eco-enzyme, a valuable and environmentally friendly product. The activities included presentations on waste management issues, hands- on soap-making workshops, and interactive evaluations using digital platforms like Kahoot. The results showed a significant increase in students' understanding and enthusiasm for eco-enzyme applications, as well as improved teamwork and communication skills. The initiative successfully demonstrated the potential of experiential learning in fostering environmental stewardship among students, encouraging them to become active participants in sustainable waste management practices. This program highlights the importance of integrating environmental education into school curricula and serves as a model for similar initiatives across Indonesia.